Effect of thunder-fire moxibustion combined with nursing intervention on functional recovery after surgery for fractures around the knee (雷火灸联合护理干预促进膝关节周围骨折术后功能恢复效果观察) - LI Wumei (李五妹); LIU Lanying (刘兰英); LI Zhou (李周) (中西医结合护理)
Objective To observe the effect of thunder-fire moxibustion on joint function recovery after surgery for fractures around the knee. Methods Totally 50 patients were divided into 2 groups (control group and observation group) by random number method. The control group was treated with routine treatment and nursing interventions after surgery, and the observation group was treated with thunder-fire moxibustion on the basis of routine treatment. The clinical effect of the two groups was compared. Results A total of 48 patients were followed up with complete results, including 24 cases in the control group and 24 cases in the observation group. The upper and lower diameters of the affected limb in the observation group were smaller than those in the control group after 3 and 7 days of treatment, with a significant difference(P＜0. 05). The Visual Analogue Scale (VAS) score of the observation group was significantly lower than that of the control group after 3, 5 and 7 days of treatment, with a significant difference(P＜0. 05). After 1, 3 and 5 weeks of treatment, the Hospital for Special Surgery (HSS) knee scores in two groups were higher than those before treatment (P＜0. 05), and the HSS knee score in the observation group was higher than that in the control group after 3 and 5 weeks of treatment (P＜0. 05). The range motion of the knee in the observation group was better than that of the control group after 7 days of treatment, with a significant difference(P＜0. 05). Conclusion Postoperative nursing combined with thunder-fire moxibustion can effectively reduce the swelling and pain of the affected limb, improve the range of motion and function of the knee joint, and improve the clinical treatment effect. (目的 观察雷火灸联合护理干预促进膝关节周围骨折术后关节功能恢复的效果。方法 采用随机数字表法将50例患者分为对照组和观察组。对照组给予常规治疗和护理, 观察组在对照组基础上增加雷火灸治疗。比较两组干预效果。结果 随访共得到48例患者完整结果, 对照组及观察组各24例。治疗3 d、7 d后, 观察组患者患侧上、下周径均小于对照组, 差异有统计学意义(P＜0. 05)。治疗3 d、7 d后, 观察组患者患侧VAS评分低于对照组, 差异有统计学意义(P＜0. 05)。治疗1周、3周、5周后, 观察组患者患侧膝HSS评分均较治疗前提高(P＜0. 05); 治疗3周、 5周后, 观察组患者患侧膝HSS评分高于对照组(P＜0. 05)。治疗7 d后, 观察组患者患侧膝关节活动度大于对照组, 差异有统计学意义(P＜0. 05)。结论 膝关节周围骨折术后护理配合实施雷火灸治疗, 能有效减轻患肢肿胀、疼痛, 促进康复, 改善膝关节活动度及功能, 有利于提高临床治疗效果。)